Transient severe brain stem depression during intraarterial papaverine infusion for cerebral vasospasm. - Barr, J D; Mathis, J M; Horton, J A (American Journal of Neuroradiology, 1994)
A 63-year-old woman had severe, symptomatic cerebral vasospasm secondary to subarachnoid hemorrhage. We initiated simultaneous infusions of papaverine into her left vertebral and left internal carotid arteries. Twenty-five minutes after the infusions had begun, the patient had a transient reaction of respiratory arrest followed by rapid, progressive loss of brain stem function.